Níveis de sombreamento artificial sobre as respostas fisiológicas, comportamentais, desempenho animal e características de carcaça e carne de nelore em confinamento - Ferro, Diogo Alves da Costa (2015)
This study aimed to evaluate the influence of different levels of artificial shading on the physiological, behavioral, animal performance and carcass characteristics of males and meat Nellore cattle in an intensive production system. The experiment was carried out from July to October 2014, in the experimental feedlot in the Animal Science Department at the State University of Goiás. Twenty-four double 24 m² stalls were used: six in the open air, six covered with black shading net with 30% light interception, six with shading net 50%, and six with shading net 80%, covering 6 m² in shade per stall, totaling 48 male Nellore cattle with an average initial weight of 310 kg. Temperature-humidity index and respiratory frequency were evaluated twice weekly, and behavior was evaluated fortnightly, starting at 06h00 and ending at 18h00, in a total of 12 h of evaluation. Feeding, rumination, rest, other activities, social, body care, playful, and abnormal behaviors were observed. The feed supplied to the animals and the orts left in the trough were weighed daily to determine their intake. Animals were weighed at the onset of the experiment and another three times until its end, followed by slaughter and assessments of characteristics and carcass and meat quality. The lowest values for temperature-humidity index and respiratory frequency were found in the stalls and animals under shading net with 80 and 50% light interception. There was no significant difference between the feeding and rumination times and frequencies of urination, defecation, self-cleaning act, and social and abnormal behaviors between the animals kept without and with access to artificial shading. Rest, other activities, and playful behaviors did not differ between the animals kept in the stalls with 30, 50, and 80% of light interception. No significant difference was observed between feed intake, initial weight, final weight, total weight gain, average daily weight gain, carcass dressing, marbling, texture, fat cover degree, subcutaneous fat thickness, loin-eye area, meat color, length and circumference thigh and leg, or carcass length of the animals in the different treatments. The use of artificial shading had no significant effect on most behavioral variables, performance, and meat quality of feedlot Nellore cattle, as the ambient temperature remained within the thermal comfort zone.